Considérer les stress urbains comme potentielles sources de désastres et de catastrophes : cas de l’habitat lacustre de Ganvié au Bénin - Fèmy A. D. D. Fagla; Alexia Pilon Diabaté; Yona Jébrak (VertigO, 2023)
By situating the urban as a human invention that adapts over time, our article addresses the perception of urban disaster resulting not from shocks, but rather from stress. Our conceptual framework demonstrates that beyond the psychosocial scale, there are stresses that arise from existing interactions between organizational social institutions, the forms of development designed and the different urbanities experienced. We will call this type of stress “stress related to urban systems” or “urban stress”. It should be noted here that the word “urban” used to weight these stresses comes from the work of Louis Wirth (1938) on the urban phenomenon. Our development will start from the analytical assessment of the lake city of Ganvié located in the south of Benin and which is inscribed on the tentative list of world heritage. Its particularity is to be a vernacular habitat born from a process of ethnocultural resilience. With very strong demographic growth, it is experiencing issues of abrupt transformation that lead to a systematic qualitative decline in the standard of living of its population. Taking it as a case study, the objective is to share empirical values ​​on a time scale between 2000 and 2016. These acquired experiences serve to understand why urban stresses can be considered as sources of disasters or catastrophes, as do shocks. Similarly, they demonstrate how urban stresses would be a beneficial asset for the persistence of a built environment.